e-Science Open, Social and Virtual Technology for Research Collaboration - Koschtial, Claudia; Köhler, Thomas; Felden, Carsten (Progress in IS,, 2021)
This open access book shows the breadth and various facets of e-Science, while also illustrating their shared core. Changes in scientific work are driven by the shift to grid-based worlds, the use of information and communication systems, and the existential infrastructure, which includes global collaboration. In this context, the book addresses emerging issues such as open access, collaboration and virtual communities and highlights the diverse range of developments associated with e-Science. As such, it will be of interest to researchers and scholars in the fields of information technology and knowledge management.